POTENSI PENULARAN COVID-19 BERDASARKAN AKTIFITAS MASYARAKAT DI KECAMATAN MAWASANGKA TAHUN 2021 - Lidya Noviyati Imaeni; Jumakil Jumakil; Jusniar Rusli Afa (Endemis Journal, 2022)
COVID-19 is a new type of disease caused by infection with the Severe Acture Respiratory Sydrome Virus 2 (SARS-COV-2) which was discovered in 2019. Community activities have the potential to transmit coronavirus disease at this time. The purpose of this study was to describe the potential transmission of Covid-19 based on community activities in Mawasangka District. The method in this research is descriptive research with a quantitative approach in drawing conclusions. The sample in this study amounted to 379 respondents. Sampling was done by proportional stratified random sampling technique. This data was collected using a questionnaire that was filled in via a google form and some of it was distributed manually. Statistical test using univariate analysis test. The results of this study indicate that community activities in the mosque have 243 respondents (64.1%) who have the potential and 136 respondents (35.9%) who have less potential to transmit Covid-19, and the travel history of the community is 109 respondents (28.8%). potential and 270 respondents (71.2%) who have less potential to transmit Covid-19. The conclusion is that community activities at the mosque have the potential to transmit Covid-19 and the travel history of the community has less potential to transmit Covid-19 in Mawasangka District.